Effectiveness of the internal audit system in second-tier banks of the Republic of Kazakhstan: a structural model - Lambekova, A.N. (BUKETOV BUSINESS REVIEW, 2021)
Object: to develop a conceptual structural internal audit model on the basis of identifying main internal audit problems that affect the financial stability of second-tier banks, and assessing the credit portfolio Methods: The research framework was scientific methodological approaches and study methods such as comparison, grouping, analysis, classification, statistical methods, induction, deduction, modeling, and economic and mathematical methods. Findings: based on the analysis of internal audit problems, credit portfolio, and questionnaire results using the Smart PLS software, a conceptual structural model of internal audit has been developed. This allows banks to determine which independent variables of internal audit (volume and standards of internal audit, credit risk assessment, annual risk-oriented audit plan, and risk management) allow financial stability. According to the first hypothesis, the credit risk assessment had an average negative impact on the financial result (- 0.364). This means that an increase in credit risk reduces the stability of the financial situation. As a result of the second hypothesis, the internal audit standard had a significant impact on the change in the financial result (0.632). That is, we see that the second-tier banks apply the internal audit standard. In addition, the third confirmed hypothesis means that the high volume of work of internal auditors had a significant impact on the change in the stability of the financial position (0.556). However, the fourth and fifth hypotheses were not confirmed. Their determination coefficients (0.091) and (0.103) remain weak. That is, this suggests that the reason for the refuted hypotheses is that the risk-oriented annual internal audit plan and the risk management system do not function sufficiently in the STB of the Republic of Kazakhstan. Conclusions: on the basis of the Smart PLS software, considering the assessment of internal audit issues, credit portfolio analysis and the questionnaire results, a conceptual structural model of internal audit has been developed. This helps establish the influence of independent internal audit variables on the bank’s financial stability.